Analysis of the influence of work discipline and work environment on employee performance of PT. Dana Purna Investama in 2022 - Annisa Octavianti; Adrian Adrian; Henry Waidan Frederick; Dwi Listyowati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This study aims to analyze Work Discipline and Work Environment on Employee Performance at PT Dana Purna Investama Jakarta. The variables studied were work discipline (X1), work environment (X2), and employee performance (Y). The type of research used was quantitative research and primary data. The technique of collecting research data is through the questionnaire method. Furthermore, the sampling technique used was purposive sampling, with the number of respondents being fifty-one (51) people. Data analysis in this study used SPSS version 26.0. The analysis used in this research is a validity test, reliability test, multicollinearity test, heteroscedasticity test, normality test, multiple linear analysis, t-test, F test, and coefficient of determination (r2). The results of testing and analysis of this study indicate that the independent variable (X), namely work discipline and work environment, simultaneously or together significantly influences the dependent variable (Y), namely employee performance. Work discipline and work environment will improve employee performance in doing the job properly and correctly to increase the company’s value compared to other companies.